2018
DOI: 10.1103/physrevd.98.063530
|View full text |Cite
|
Sign up to set email alerts
|

New general parametrization of quintessence fields and its observational constraints

Abstract: We present a new parameterization of quintessence potentials for dark energy based directly upon the dynamical properties of the equations of motion. Such parameterization arises naturally once the equations of motion are written as a dynamical system in terms of properly defined polar variables. We have identified two different classes of parameters, and we dubbed them as dynamical and passive parameters. The dynamical parameters appear explicitly in the equations of motion, but the passive parameters play ju… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 81 publications
(112 reference statements)
2
43
0
Order By: Relevance
“…While there is no evidence in favour of dynamics, there is also no evidence against dynamics of quintessence kind, as opposed to the claim disfavouring quintessence [21]. More recently, [113] have commented on the nature of the arbitrariness in the choices for quintessence potentials and claimed they are indistinguishable, since current data can constrain neither the potential param-eters nor initial conditions (what they call active and passive parameters respectively). Their study is based on parametrizing V (φ), similarly to the approach of [58].…”
Section: Model Selectionmentioning
confidence: 90%
“…While there is no evidence in favour of dynamics, there is also no evidence against dynamics of quintessence kind, as opposed to the claim disfavouring quintessence [21]. More recently, [113] have commented on the nature of the arbitrariness in the choices for quintessence potentials and claimed they are indistinguishable, since current data can constrain neither the potential param-eters nor initial conditions (what they call active and passive parameters respectively). Their study is based on parametrizing V (φ), similarly to the approach of [58].…”
Section: Model Selectionmentioning
confidence: 90%
“…The barotropic equation of state takes the usual values of γ j = 1/3 for a relativistic species and γ j = 0 for a non-relativistic one. We define a new set of polar coordinates in the form [15][16][17][18][19][20][21][22],…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…where the α are just constant parameters. This parametrization includes a large class of quintessence potentials (see Table 1 and 2 in [15]).…”
Section: General Tracker Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dot denotes derivative with respect to cosmic time t , and H=a˙/a is the Hubble parameter. By introducing the following change of variables (Cedeño et al 2017; Copeland et al 1998; Linares Cedeño et al 2020; Roy et al 2018; Ureã López 2016; Ureña López & González‐Morales 2016), normalΩϕ1/2sinθ/2=κϕ˙6H,normalΩϕ1/2cosθ/2=κV1/23H, y122HϕV1/2,y243Hκϕ2V1/2, it can be shown that the Klein‐Gordon equation is written as θ=3sinθ+y1, normalΩϕ=3witalictotwϕnormalΩϕ, y1=321+witalictoty1+normalΩ...…”
Section: Background Evolutionmentioning
confidence: 99%